A cross-sectional evaluation examining the use of the Achilles tendinopathy toolkit by physiotherapists in British Columbia, Canada. Issue 7 (27th March 2017) - Ezzat, Allison M.; Schneeberg, Amy; Huisman, Elise S.; White, Lynita D.; Kennedy, Carol; Levesque, Lenerdene A.; Scott, Alex; Hoens, Alison M.
Abstract: Purpose : To evaluate the awareness and use of the Achilles tendinopathy toolkit (ATT), a knowledge translation (KT) strategy supporting evidence-informed management of midportion Achilles Tendinopathy (AT), by British Columbian physiotherapists (PTs). Secondarily, to assess PTs strategies for AT management by examining the association between exploring the ATT and following best practice in clinical care as recommended by the ATT.Methods : Members of the Physiotherapy Association of British Columbia (BC) completed an online cross-sectional survey collecting information on demographics; awareness and exposure; perceptions, usability and applicability to clinical practice; knowledge; and attitudes. A clinical vignette assessed if respondents adhered to recommendations made by the ATT. Multi-variable logistic regression examined the association between exploring the ATT and following its recommendations.Results : Of 238 participants, 81% ( n = 154) were aware of the ATT and of those 53% ( n = 81) explored its contents. Time was the most frequent barrier. Bi-variable analyses showed those who explored the ATT had over double the odds of following the best practice (odds ratio = OR = 2.8; 95% confidence interval = 95% CI = 1.3–6.0). This did not remain significant in the final adjusted model (OR = 2.2; 95% CI = 0.9–5.4).Conclusions : Evaluation of KT strategies is critical. This study revealed high awareness and moderate use of the ATT. Future work should consider the impact of toolkits on patient outcomes. Implications for Rehabilitation: A toolkit is a novel knowledge translation (KT) strategy designed to provide accessibleevidence-informed resources to facilitate best practice by clinicians. The evaluation of the Achilles tendinopathy toolkit (ATT) revealed favourable findingsregarding the impact of this KT strategy on the knowledge and attitudes of British Columbia(BC) PTs and the possibility of a positive impact on best practice in clinical care. This research suggests toolkits are a feasible and meaningful KT strategy to provide clinicianswith valuable synthesized resources that have the potential to benefit patient outcomes.